2015
DOI: 10.1111/nan.12259
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent mutations of CD79B and MYD88 are the hallmark of primary central nervous system lymphomas

Abstract: The prevalence of CD79B and MYD88 mutations in PCNSLs was considerably higher than reported in systemic diffuse large B-cell lymphomas. This observation could reflect the paucity of antigen stimuli from the immune system in the central nervous system (CNS) and the necessity to substitute them by the constitutive activation of CD79B and MYD88 that would initiate the signalling cascades. These hotspot mutations may serve as a genetic hallmark for PCNSL serving as a genetic marker for diagnose and potential targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
157
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 27 publications
17
157
2
2
Order By: Relevance
“…Twenty-nine studies have reported that the frequency of MYD88 L265P mutation in 2285 DLBCL patients except for central nervous system (CNS) and testicular lymphomas was 16.5% (95% CI: 11.9–22.6%) 2, 3, 6, 7, 911, 13, 1622, 24, 25, 27, 28, 30, 31, 33–39, 41 . Thirteen 4, 5, 8, 9, 12, 14, 15, 18, 21, 23, 26, 32, 40 and four 8, 9, 21, 29 studies reported the prevalence of MYD88 L265P mutation in 378 CNS and 88 testicular DLBCL patients. The MYD88 L265P mutation in the CNS and testis were detected in 59.8% (95% CI: 42.2–75.2%) and 77.1% (95% CI: 67.1–84.7%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine studies have reported that the frequency of MYD88 L265P mutation in 2285 DLBCL patients except for central nervous system (CNS) and testicular lymphomas was 16.5% (95% CI: 11.9–22.6%) 2, 3, 6, 7, 911, 13, 1622, 24, 25, 27, 28, 30, 31, 33–39, 41 . Thirteen 4, 5, 8, 9, 12, 14, 15, 18, 21, 23, 26, 32, 40 and four 8, 9, 21, 29 studies reported the prevalence of MYD88 L265P mutation in 378 CNS and 88 testicular DLBCL patients. The MYD88 L265P mutation in the CNS and testis were detected in 59.8% (95% CI: 42.2–75.2%) and 77.1% (95% CI: 67.1–84.7%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The frequent utilization of V H 4-34 in ABC DLBCL cases is consistent with previous work demonstrating an enrichment for V H 4-34 among DLBCL cases classified as "non-GCB" by immunostaining (20). Primary central nervous system lymphoma (PCNSL) is a type of DLBCL that has an ABC phenotype (38) and acquires several of the pathognomonic mutations of ABC DLBCL (39)(40)(41)(42). V H 4-34 is used in 55% of PCNSL cases, an enrichment that suggests that this V H segment confers a selective advantage in PCNSL, as in nodal ABC DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that a high frequency (>75%) of MYD88 L265P mutations (an adaptor protein mediating toll-like receptor and interleukin-1 signaling) in the DLBCL subtype of PCNSL may be an initiator of disease. Additionally, most MYD88 L265P-positive patients have CD79B or CARD11 mutations (B cell receptor signaling pathway)282930. In addition, the constitutive activation of the nuclear factor (NF)- κB pathway is a hallmark of B cell PCNSL31.…”
Section: Discussionmentioning
confidence: 99%